2018
DOI: 10.1248/bpb.b17-00837
|View full text |Cite
|
Sign up to set email alerts
|

Dibenzoylmethane Suppresses Lipid Accumulation and Reactive Oxygen Species Production through Regulation of Nuclear Factor (Erythroid-Derived 2)-Like 2 and Insulin Signaling in Adipocytes

Abstract: The aim of this study was to investigate the effects of dibenzoylmethane (1,3-diphenyl-1,3-propanedione, DBM) from licorice roots on lipid accumulation and reactive oxygen species (ROS) production in 3T3-L1 cells. DBM effectively inhibited lipid accumulation during adipogenesis, and its inhibitory effect was shown to be due to the down-regulation of adipogenic factors such as CCAAT-enhancer-binding protein-α (C/EBPα), peroxisome proliferator-activated receptor γ (PPARγ), and fatty acid-binding protein 4 (FABP4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…3T3‐L1 cells were grown and maintained in DMEM containing 10% BS and 1% PS. Two days after confluency, adipocyte differentiation (adipogenesis) was induced and processed as previously described . RAW264.7 cells, a murine blood macrophage cell line, were plated at 2 × 10 5 cells per well and cultured in 10% FBS/1% PS‐supplemented DMEM.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…3T3‐L1 cells were grown and maintained in DMEM containing 10% BS and 1% PS. Two days after confluency, adipocyte differentiation (adipogenesis) was induced and processed as previously described . RAW264.7 cells, a murine blood macrophage cell line, were plated at 2 × 10 5 cells per well and cultured in 10% FBS/1% PS‐supplemented DMEM.…”
Section: Methodsmentioning
confidence: 99%
“…RAW264.7 or 3T3‐L1 cells (1.5 × 10 4 cells per well) were incubated in a 96‐well plate for 24 h. Cells were pretreated with PCG (1–10 µ m ) for 2 h, after which the medium was replaced with ACM. After 24–48 h, the MTT assay was performed as previously described …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, ROS generation has also been a mechanism associated with the monocyte-tomacrophage differentiation. [42][43][44] Many studies showed that ROS is critically produced during macrophage differentiation, but ROS removal or elimination blocks the macrophage differentiation. [42][43][44] Based on our previous study showing that DBM suppressed intracellular ROS generations, 45) DBM-mediated inhibition of differentiation of monocyte to macrophage is also considered to be due to the ROS regulation.…”
Section: Discussionmentioning
confidence: 99%